Draft Annual Plan (2003-2004) Government of Jammu and Kashmir - Planning Commission (Planning Commission, 2003)
Jammu & Kashmir is one of the most sparsely populated State of the Indian Union, even though it has registered a higher rate of growth of population in the recent past than that of the country as a whole. The density of population, according to the latest census, is 99 persons per square kilometer. The total population as per the census of 2001 is 100.69 lacs, 43.96 lacs in Jammu region. 54.41 lacs in Kashmir region and 2.33 lacs in Ladakh region. The area is 222236 Sq. Kms which includes 78114 Sq. Kms under illegal occupation of PoK. 5180 Sq. Kms illegally handed over by Pakistan to China and 37.55 Sq. kms under illegal occupation of China in Leh District.
Government of Jammu and Kashmir